2003
DOI: 10.1103/physrevlett.90.014501
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Turbulence in Particulate Pipe Flow

Abstract: We investigate experimentally the influence of suspended particles on the transition to turbulence. The particles are monodisperse and neutrally-buoyant with the liquid. The role of the particles on the transition depends both upon the pipe to particle diameter ratios and the concentration. For large pipe-to-particle diameter ratios the transition is delayed while it is lowered for small ratios. A scaling is proposed to collapse the departure from the critical Reynolds number for pure fluid as a function of co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
136
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(161 citation statements)
references
References 15 publications
(15 reference statements)
23
136
1
1
Order By: Relevance
“…This was shown for fixed (but force-free) cylinders and spheres by Bottin et al (1997Bottin et al ( , 1998, while Matas, Morris & Guazzelli et al (2003) have shown that neutrally buoyant, and presumably on average force-free, suspended spherical particles at dilute conditions lead to laminar-turbulent transition in a pipe at substantially lower pipe Reynolds number than observed for the pure fluid. In the latter of these studies, particle-scale inertia was argued to play a role as pronounced effects of the dilute particles were seen only for Re = O(1).…”
Section: Discussionmentioning
confidence: 99%
“…This was shown for fixed (but force-free) cylinders and spheres by Bottin et al (1997Bottin et al ( , 1998, while Matas, Morris & Guazzelli et al (2003) have shown that neutrally buoyant, and presumably on average force-free, suspended spherical particles at dilute conditions lead to laminar-turbulent transition in a pipe at substantially lower pipe Reynolds number than observed for the pure fluid. In the latter of these studies, particle-scale inertia was argued to play a role as pronounced effects of the dilute particles were seen only for Re = O(1).…”
Section: Discussionmentioning
confidence: 99%
“…For the highest solids fraction examined in this study, the apparent viscosity was almost double that of the suspending liquid. Equation (1) with C m ¼ 0:65 [20] captures the data satisfactorily. Using a force balance between the drag and buoyancy for the single rising bubble yields the following expression for the bubble velocity:…”
Section: -2mentioning
confidence: 99%
“…The different rheological behavior is often associated with the slurry internal structure [22][23][24][25]. At low shear rates, free water is immobilized in void spaces within flocs and the floc network.…”
Section: Rheological Propertiesmentioning
confidence: 99%